Lactic Acid Bacteria 2014
DOI: 10.1007/978-94-017-8841-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Lactic Acid Bacteria

Abstract: Lactic acid bacteria (LAB) are 'generally recognised as safe' microorganisms, and some of them were given the 'Qualified Presumption of Safety' status by the European Food Safety Authority. Due to their significant contribution to various industrial applications, many of these organisms were subjected to full genome sequencing projects. Together with the increased amount of published transcriptomics and proteomics data across the entire genome, we have unprecedented opportunities to revisit the important trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 177 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Plasmids are most commonly present in different LAB species, involved in 11 genera, including Bifidobacterium , Brevibacterium , Enterococcus , Lactobacillus , Lactococcus , Leuconostoc , Oenococcus , Pediococcus , Streptococcus , Tetragenococcus , and Weissella . LAB plasmids are extremely diverse in terms of size (0.87 kb to more than 250 kb), copy number (from 1 to more than 100 plasmids per cell), and phenotypes conferred to their hosts [ 5 , 6 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Diversity and Similarity Of Plasmids From Labmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids are most commonly present in different LAB species, involved in 11 genera, including Bifidobacterium , Brevibacterium , Enterococcus , Lactobacillus , Lactococcus , Leuconostoc , Oenococcus , Pediococcus , Streptococcus , Tetragenococcus , and Weissella . LAB plasmids are extremely diverse in terms of size (0.87 kb to more than 250 kb), copy number (from 1 to more than 100 plasmids per cell), and phenotypes conferred to their hosts [ 5 , 6 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Diversity and Similarity Of Plasmids From Labmentioning
confidence: 99%
“…A large number of plasmids were isolated and characterized from different sources of LAB as self-replicating extrachromosomal genetic materials [ 4 ]. Although most plasmids remain cryptic, some plasmids have been found that are associated with many important functions of LAB species, including (1) hydrolysis of proteins; (2) amino acid, citrate, and carbohydrate metabolism (e.g., lactose/galactose utilization, and oligopeptide transport); (3) production of bacteriocin, exopolysaccharide, and pigments; (4) resistance to antibiotic, bacteriophage, heavy metal, and other stress responses; and (5) DNA restriction-modification systems [ 4 , 5 , 6 , 7 , 8 ]. A variety of industrially relevant characteristics are encoded on the LAB plasmids, including the degradation of casein, acidification by lactic acid, and production of flavor compounds, which contribute to the desired flavor and texture of the fermentation product and to optimal growth of strains in milk [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria (LAB) is a naturally biodiverse, well-established group of microorganisms widely used in food industry and of well-documented impact on human health (Wu et al 2017 ). LABs are “generally recognized as safe” (GRAS) in the USA and given the “Qualified Presumption of Safety” (QPS) status by the European Food Safety Authority (EFSA) (Zhang and Zhang 2014 ). They were isolated from various ecological niches, starting from the gastrointestinal tracts of humans, animals, and insects, through plant- and meat-based materials, to soil and water (Hammes and Hertel 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The industrial and technological relevance of LAB strains motivated extensive genomic studies, which have provided significant insight into their metabolism, physiology, and potential for new applications (Zhang and Zhang 2014 ; Bosma et al 2017 ). Since 2001, when the first LAB genome was published (Bolotin et al 2001 ), hundreds of LAB genomes have been sequenced and are publicly available at different assembly levels (Sun et al 2015 ; Zheng et al 2015 ; Wu et al 2017 ; Salvetti et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%